Radiation resistance of nano-structured tungsten-rhenium sheet - Armstrong, D; Roberts, S (Materials Research Society, 2013)
Tungsten is one the most important material for both plasma facing and structural applications in current designs for advanced divertors. Recent work has shown that composites can be manufactured from nanostructured tungsten foils which show significantly higher toughness than monolithic tungsten, but there is no data on the radiation resistance of such materials. In this study W-5 wt% Re foil in both an as rolled and annealed condition was implanted with 2MeV W+ ions to two damage levels, 0.07 and 0.4 dpa. The change in hardness was measured using nanoindentation. An increase in hardness was seen in both materials at both damage levels, with more hardening seen for the 0.4 dpa implanted samples. However the increase in hardness due to ion implantation was 2.6 times higher in the annealed material as compared to the as rolled material. This is due to the smaller grain size and higher dislocation density providing more sinks for the irradiation produced defects in the as rolled material as compared to the annealed material. Thus showing that unannealed tungsten foils are superior for use in applications in which they will see significant levels of radiation damage. © 2013 Materials Research Society.